The Trotula : an English translation of the medieval compendium of women's medicine - Green, Monica Helen; Green, Monica Helen (Middle Ages series., 2002)
The Trotula was the most influential compendium on women's medicine in medieval Europe. Green here presents the first modern English translation of the so-called standardized Trotula ensemble, a composite form of the texts that was produced in the mid-thirteenth century and circulated widely in learned circles.